∫ 0 ∞ x sin 3 x sin 5 x d x = ?
Notation: lo g ( ⋅ ) denotes natural logarithm (logarithm to the base e ).
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let: I = 0 ∫ ∞ x sin 3 x sin 5 x d x = 2 1 0 ∫ ∞ x cos 2 x − cos 8 x d x = 2 1 0 ∫ ∞ x f ( a x ) − f ( b x ) d x , where f ( x ) = cos x , a = 2 and b = 8 .
(Now we use the results established by Frullani for integrals of the form: 0 ∫ ∞ x f ( a x ) − f ( b x ) d x , where f is a continuous function in R + and a , b ∈ R + .
See here for Frullani Theorem . Refer conditions C 1 and C 3 . They are applicable in this case as f ( x ) = cos x satisfies them both).
Thus, by using the result when conditions C 1 and C 3 applicable:
I = 2 1 ( x → 0 lim f ( x ) ) lo g a b = 2 1 lo g 4 = lo g 2
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Differentiation Under the Integral Sign
Define the function F ( s ) = ∫ 0 ∞ x sin 3 x sin 5 x e − s x d x . Notice that the integral we want to find is F ( 0 ) which we may compute if we are able to find another expression for F . For this, compute F ′ ( s ) = ∫ 0 ∞ x sin 3 x sin 5 x e − s x ( − x ) d x = − ∫ 0 ∞ sin 3 x sin 5 x e − s x d x . To be able to compute this integral first apply the identity sin 3 x sin 5 x = 2 1 ( cos 2 x − cos 8 x ) so we have F ′ ( s ) = 2 1 ∫ 0 ∞ ( cos 8 x − cos 2 x ) e − s x d x . These are now standard integrals the reader should be able to compute, but if one knows about Laplace transforms then this can be written as F ′ ( s ) = 2 1 ( L ( cos 8 x ) − L ( cos 2 x ) ) and using the known formulas one can find that this is equal to F ′ ( s ) = 2 1 ( s 2 + 8 2 s − s 2 + 2 2 s )
To find F ( s ) we want to integrate this with respect to s which we may do by first computing ∫ s 2 + a 2 s d s . Let u = s 2 + a 2 so d u = 2 s d s ⟹ s d s = 2 d u so the integral is equal to 2 1 ∫ u d u = 2 1 lo g u = 2 1 lo g ( s 2 + a 2 ) . Applying this result we get that:
F ( s ) = 4 1 ( lo g ( s 2 + 8 2 ) − lo g ( s 2 + 2 2 ) ) + C where C is some constant. To find what C is we just need a little more information about F ( s ) . Notice that according to the current expression for F ( s ) , lim s → ∞ F ( s ) = C . But we can compute this limit using the original definition:
0 ≤ ∣ ∣ ∫ 0 ∞ x sin 3 x sin 5 x e − s x d x ∣ ∣ ≤ ∫ 0 ∞ ∣ ∣ x sin 3 x sin 5 x e − s x ∣ ∣ d x ≤ ∫ 0 ∞ 3 e − s x d x = s 3 → 0 as s → ∞ .
According to the previous chain of inequalities and the Squeeze Theorem, this limit is 0 which implies C = 0 so we can finally say that F ( s ) = 4 1 ( lo g ( s 2 + 8 2 ) − lo g ( s 2 + 2 2 ) ) and
F ( 0 ) = 4 1 lo g ( 2 2 8 2 ) = 4 1 lo g 1 6 = 4 1 lo g ( 2 4 ) = lo g 2 .